2010
DOI: 10.1111/j.1467-8624.2010.01516.x
|View full text |Cite
|
Sign up to set email alerts
|

Reading Minds: The Relation Between Children’s Mental State Knowledge and Their Metaknowledge About Reading

Abstract: The relation between children's mental state knowledge and metaknowledge about reading was examined in 2 studies. In Study 1, 196 children (mean age = 9 years) were tested for verbal ability (VA), metaknowledge about reading, and mental state words in a story task. In Study 2, the results of Study 1 were extended by using a cross-lagged design and by investigating older children (N = 71, mean ages = 10 years at Time 1 and 11 years at Time 2) for mental state knowledge, metaknowledge about reading, and VA. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
61
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 56 publications
9
61
1
2
Order By: Relevance
“…Although Lecce, Zocchi, Pagnin, Palladino, and Taumoepeau (2010) work focused on children older than those considered in the current study, and on metacognition applied to a reading comprehension task, we expected to find similar results with respect to DM. There are three main reasons for expecting DM to be more closely related to cognitive ToM than to affective ToM.…”
Section: Specificity Of the Relation Between Tom And Dmmentioning
confidence: 54%
See 1 more Smart Citation
“…Although Lecce, Zocchi, Pagnin, Palladino, and Taumoepeau (2010) work focused on children older than those considered in the current study, and on metacognition applied to a reading comprehension task, we expected to find similar results with respect to DM. There are three main reasons for expecting DM to be more closely related to cognitive ToM than to affective ToM.…”
Section: Specificity Of the Relation Between Tom And Dmmentioning
confidence: 54%
“…This research, conducted by Lecce and colleagues (Lecce, Zocchi, Pagnin, Palladino, & Taumoepeau, 2010), involved a sample of Italian primary school children. It focused on children's metaknowledge about reading comprehension and showed that whereas cognitive ToM (indexed by cognitive mental state language and the Strange Stories task) was significantly associated with metaknowledge about reading, affective ToM (indexed by emotion mental state language and the Test of Emotion Comprehension) was not.…”
Section: Specificity Of the Relation Between Tom And Dmmentioning
confidence: 99%
“…Thus, metacognitive knowledge could mediate between children's theory of mind and academic performance. Longitudinal studies demonstrated that children's theory of mind is predictive for children's metacomprehension (Lecce, Zocchi, Pagnin, Palladino, & Taumoepeau, 2010) and metamemory (Ebert, 2011;Lecce, Demicheli, Zocchi, & Palladino, 2015;Lockl & Schneider, 2007a) which holds true even if earlier scores on metamemory were controlled for (Ebert, 2015). In a similar vein, another possible mechanism suggesting an association between theory of mind and academic achievement could be children's beliefs about learning.…”
Section: Introductionmentioning
confidence: 90%
“…For example, according to Kuhn (2000), meta-knowing includes both theory of mind and metacognition; the former encompasses declarative knowledge, whereas the latter encompasses procedural knowledge. Supporting this proposal, longitudinal studies demonstrate predictive links between false belief understanding and children's later metamemory (Lockl & Schneider, 2007) and metacomprehension (Lecce, Zocchi, Pagnin, Palladino, & Taumoepeau, 2010).…”
Section: Introductionmentioning
confidence: 89%